2014
DOI: 10.1249/mss.0000000000000138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dynamic Stretching on Strength, Muscle Imbalance, and Muscle Activation

Abstract: Because dynamic stretching reduced concentric and eccentric hamstring strength as well as the conventional and functional H:Q ratios, fitness and allied-health professionals may need to be cautious when recommending dynamic rather than static stretching to maintain muscle force.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 42 publications
(100 reference statements)
2
41
2
3
Order By: Relevance
“…S1b 1 ) revealed that the weighted mean performance enhancement associated with DS was 1.3%. Unsurprisingly, given the modest changes, almost one-half of the measurements (37 of 80) demonstrated trivial magnitude changes, with only 6 studies reporting subsequent small-to-large relative performance impairments Bacurau et al 2009;Curry et al 2009;Barroso et al 2012;Franco et al 2012;Costa et al 2014). Thus, although there are occasions in which moderate or large improvements in performance are reported, overall, no robust evidence exists for substantial performance enhancements after DS.…”
Section: Dynamic Stretchingmentioning
confidence: 99%
See 1 more Smart Citation
“…S1b 1 ) revealed that the weighted mean performance enhancement associated with DS was 1.3%. Unsurprisingly, given the modest changes, almost one-half of the measurements (37 of 80) demonstrated trivial magnitude changes, with only 6 studies reporting subsequent small-to-large relative performance impairments Bacurau et al 2009;Curry et al 2009;Barroso et al 2012;Franco et al 2012;Costa et al 2014). Thus, although there are occasions in which moderate or large improvements in performance are reported, overall, no robust evidence exists for substantial performance enhancements after DS.…”
Section: Dynamic Stretchingmentioning
confidence: 99%
“…Two studies reporting performance impairments required subjects to perform small ballistic bouncing or bobbing movements near the end ROM Bacurau et al 2009). Studies using "exaggerated movements", which may or may not reach the end of the active ROM, report both performance impairments (Costa et al 2014) and no significant effect (Dalrymple et al 2010). Thus, there is no identifiable trend as to the effects associated with DS through a full (maximal) or nearly full (submaximal) ROM.…”
Section: Effect Of Magnitude Of Ds Movement On Performancementioning
confidence: 99%
“…However, Aboodarda et al (2014) found that elbow flexor fatigue increased rather than decreased leg extensor spinal motoneuron excitability. Similar to NLMF, SS-induced performance impairments have been at least partially attributed to neural mechanisms (Behm et al 2013;Behm and Chaouachi 2011;Costa et al 2014). DS has been shown to enhance subsequent performance (Behm and Chaouachi 2011;Costa et al 2014;Herda et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, both static and PNF stretching are preferred in a situation in which the goal is to improve flexibility [18]. Dynamic stretching, which involves the execution of movement patterns throughout the available range of motion (ROM), is more suitable for warm-up routines [5].…”
Section: Types Of Stretchingmentioning
confidence: 99%
“…The most popular strategy used to enhance flexibility is stretching [2], which can be performed either statically [3,4] or dynamically [5]. Stretching is a strategy commonly employed in both training and rehabilitation programs [2] and it is used often in warm-up routines [6].…”
Section: Introductionmentioning
confidence: 99%